Effect of plastic deformation on the hydrogen embrittlement of ferritic high strength steel - Tim Boot; Pascal Kömmelt; Ruud W. A. Hendrikx; Amarante J. Böttger; Vera Popovich (npj Materials Degradation)
Abstract The effect of hydrogen charging during plastic deformation was investigated on a ferritic steel containing TiC nano-precipitates. Specimens were subjected to a slow strain rate tensile test (SSRT) up to 0, 1, or 3% plastic engineering strain, held until a total duration of 2 h to saturate with hydrogen, then fast fractured. The specimens pre-strained elastically absorbed 2.36 wppm of hydrogen, which increased to 3.69 wppm for 3% plastic strain. Only 0.72 wppm is stored in non-dislocation traps such as precipitates, grain boundaries, and lattice sites, which makes dislocations the main contributor to hydrogen trapping. The increased hydrogen uptake did not lead to a decrease in fracture strain, which remained between 6 and 10% for all pre-strains, compared to 60% for full SSRT tests that were charged for a shorter time. This research highlights the necessity of high plastic strains and the presence of hydrogen in the environment during crack growth to cause HE in ductile steels.